The emergence of chordin-like1 in gnathostomes may have contributed to the evolution of paired appendages - Ermakova, Galina V.; Meyntser, Irina V.; Mugue, Nikolai S.; Lyubetsky, Vassily A.; Zaraisky, Andrey G.; Bayramov, Andrey V. (Frontiers in Cell and Developmental Biology, 2025)
Genomic transformations during early vertebrate evolution, including two rounds of whole-genome duplication, laid the groundwork for the emergence of novel morphological features in jawed vertebrates. Among these innovations, paired appendages represent a major evolutionary milestone, whose development and diversification enabled vertebrates to exploit diverse ecological niches in aquatic, terrestrial, and aerial environments. Here, we combined phylogenetic and local genomic synteny analyses to investigate the evolutionary history of chordin-like homologs in vertebrates. Our results indicate that chordin-like1 first appeared in jawed vertebrates, suggesting a possible link between its origin and the emergence of paired appendages. To explore this hypothesis, we examined chordin-like1 expression in representatives of basal jawed vertebrate lineages - cartilaginous fishes (grey catshark, Chiloscyllium griseum) and sturgeons (sterlet, Acipenser ruthenus). We further assessed the expression and functional properties of the chordin-like1 ortholog in the African clawed frog (Xenopus laevis), a representative terrestrial vertebrate with limb morphology that markedly differs from the fins of basal gnathostomes. Together with published data, our findings support a potential role for chordin-like1 in the evolution of paired appendages. In particular, chordin-like1 may have contributed to the development of the metapterygial element and its derivatives, which formed the structural basis for the evolution of tetrapod limbs.